Four new cavernicolous species of the millipede genus Eutrichodesmus Silvestri, 1910 from southern China (Diplopoda: Polydesmida: Haplodesmidae) - Liu, Weixin; Tian, Mingyi (Zootaxa, 2013)
Four new species of the large oriental genus Eutrichodesmus Silvestri, 1910 are described from caves in southern China: E. digitatus sp. n. (Guangdong), E. simplex sp. n. (Jiangxi), E. spinatus sp. n. (Hunan) and E. planatus sp. n. (Guangxi).